Impact of cancer types on COVID-19 infection and mortality risk: a protocol for systematic review and meta-analysis. Issue 7 (8th July 2022) - Zou, Jianhua; Xiao, Zhanshuo; Yang, Jingyan; Li, Liusheng; Hao, Tengteng; Cui, Ning; Wu, Jiao; Wu, Yu
Abstract : Introduction: The COVID-19 pandemic has created a huge social and economic burden, and the lifestyles of individuals have significantly changed. In addition, the diagnosis, treatment and management of patients with cancer were greatly affected. Studies have shown that patients with cancer are at a higher risk of COVID-19 infection-related complications, which require aggressive preventive measures. Different types of cancer may have different risks of COVID-19 infection and death, and different preventive care measures are needed for different types of patients with cancer. Here, we designed a protocol for systematic review and meta-analysis to explore the impact of cancer types on COVID-19 infection and mortality risk. Methods and analysis: A systematic search plan will be performed to filter the eligible studies in the seven databases, namely PubMed, Cochrane search strategy, EMBASE search strategy, SinoMed, China National Knowledge Infrastructure, China Science and Technology Journals Database, and Wanfang database from 2019 to 10 August 2021. Two independent reviewers will choose the eligible studies and extract the data. The risk of bias will be evaluated based on the Newcastle-Ottawa Scale recommended by the Cochrane Collaboration. Finally, a systematic review and meta-analysis will be performed using Review Manager (V.5.3) statistical software. Ethics and dissemination: Formal ethical approval is not required, and the findings will be published in a peer-reviewed journal. PROSPERO registration number: CRD42021271108.